A new planthopper family Katlasidae fam. nov. (Hemiptera: Fulgoromorpha: Fulgoroidea) from mid-Cretaceous Kachin amber. (November 2020) - Luo, Cihang; Jiang, Tian; Szwedo, Jacek; Wang, Bo; Xiao, Chuantao
Abstract: A new planthopper family Katlasidae fam. nov. is described based on a well-preserved specimen from mid-Cretaceous Kachin amber (Burmese amber). It is characterized by vertex separated from frons with two parallel, transverse carinae; antenna with pedicel densely covered with sensory lentiform flattened plaque organs; pronotum with elevated disc, complete median carina and incomplete lateral carinae; mesonotum in shape of transverse lozenge, without median and lateral carinae; tegmen widened at membrane and with dense venation on it, costal area absent, stigma area without sclerotization or veinlets, clavus closed, terminals of MP multiplied, transverse veinlets not regular, not forming distinct rows; hind wing veinlets scarce, two transverse veinlets rp-mp ; male pygofer elongate, tubular, ventrally carinate, genital styles exposed beyond ventral margin of pygofer. Only one genus and species Katlasus xiai gen. et sp. nov. has been discovered. The new family's morphological combination of characters reach beyond the known disparity of the Fulgoroidea. Important morphological characters of new taxa as antennal plaque organs, head and thorax structures, tegmen and wing structure and venation, and terminalia, as well as relationships of Katlasidae fam. nov. with other Fulgoroidea are discussed. Environmental changes, palaeoclimatic and palaeogeographical factors influencing diversification and evolutionary processes of planthoppers during the period of formation of modern faunistic complexes at mid-Cretaceous biotic re-organization times and documented in Kachin amber biota are discussed.